+0  
 
0
354
1
avatar

kann mir wer bitte erklären, wie ich die folgende Aufgabe löse? 8c(hoch)2 * d(hoch) 2 - ?= 4cd(hoch)2 * (?-3d(hoch)2)

 16.09.2016
 #1
avatar+8576 
0

kann mir wer bitte erklären, wie ich die folgende Aufgabe löse? 8c(hoch)2 * d(hoch) 2 - ?= 4cd(hoch)2 * (?-3d(hoch)2)

            

                                                         

\(8c^2d^2-?_{1}= 4cd^2\times \left(?_{2}-3d^2\right) \)

Versuch:   

\(?_{1}=4c^2d^2\)                      \(?_2=c\)  

Dann gilt:       

\(4c^2d^2\)          =  \(4c^2d^2-12cd^4\) 

\(12cd^4=0\)

laugh

\(\)            

 16.09.2016

3 Benutzer online